2004
DOI: 10.1097/00126097-200408000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of twenty-four-hour ambulatory hemodynamic bioimpedance measures in African American adolescents

Abstract: Background-The reliability of ambulatory impedance cardiography has not been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…These results showed that the vascular response to mental stress was unstable during the one-year interval (ICCϽ0.6), although the blood pressure and cardiac responses remained stable. These results agreed with those of the previous study mentioned above (Barnes et al, 2004), although Barnes et al measured the cardiovascular indexes in a freeliving environment. In addition, it can be seen that all indexes except HR showed higher ICCs over the intervals of several days than over the one-year interval.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results showed that the vascular response to mental stress was unstable during the one-year interval (ICCϽ0.6), although the blood pressure and cardiac responses remained stable. These results agreed with those of the previous study mentioned above (Barnes et al, 2004), although Barnes et al measured the cardiovascular indexes in a freeliving environment. In addition, it can be seen that all indexes except HR showed higher ICCs over the intervals of several days than over the one-year interval.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have verified the test-retest reproducibility of cardiovascular responses to mental tasks, finding significant correlations between experiment days for a certain period (Armario et al, 1995;Jern et al, 1995;Barnes et al, 2004). Other researchers indicated that the ICC was suitable for verifying reproducibility because it can measure the association strength among repetitions (Carrasco et al, 2003;Reland et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The AIM has been validated in healthy men and women (Sherwood et al, 1998;Sherwood, Hughes, & McFetridge, 2003), various ethnic groups (Barnes, Johnson, & Treiber, 2004;Bishop, Pek, & Ngau, 2005;Sherwood et al, 2003), normotensive adolescents (Barnes et al, 2004), and normotensive young adults (Bishop et al, 2005). The AIM has been found to provide valid and reliable estimates of cardiac function when compared to the impedance reference standard (Minnesota Impedance Cardiography model LVET is positively related to myocardial contractility 304B) (Sherwood et al, 1998).…”
Section: Research Measuresmentioning
confidence: 99%
“…This methodology facilitates observing real-life (at school and at home) BP, assessing the generalization of treatment effects in out-of-laboratory situations [88]. Reproducibility of ambulatory results have been validated in youth [89,90]. Findings in youth have indicated that ambulatory SBP measures are stable across periods of time varying from 1 to 4 years [91].…”
Section: Ambulatory Bp Monitoringmentioning
confidence: 99%